MENGCOUNTER HOAX MELALUI INTERNALISASI NILAI NILAI PENDIDIKAN ISLAM (Pascasarjana IAIN Kudus, 2017)
The purpose of study is to know the hoax and its impact for the community and how to counter hoax with the internalization of Islamic education. the research used is a qualitative descriptive method designed to collect information about ongoing situations. Hoax can be countered by the internalization of the value of Islamic education, technical there are two stages. First: the transformation of the value of Islamic education and the second is the applicative stage oriented to the improvement of attitudes and morals.